Do PROMs or Sensor-Based Monitoring Detect Improvements in Patients’ Knee Function After Total-Knee Arthroplasty?—A Study Protocol for a Prospective Controlled Study - Lotanna Mba; Robert Prill; Jonathan Lettner; Nikolai Ramadanov; Robert Krause; Jan Reichmann; Roland Becker (Sensors)
Determining whether preoperative performance-based knee function predicts postoperative performance-based knee function and whether patient-reported outcome measures (PROMs) completed by participants can detect these changes could significantly enhance the planning of postoperative rehabilitation for patients following total knee arthroplasty (TKA). This study aims to collect data on performance-based knee function using inertial measurement units (IMUs) worn by participants both preoperatively and postoperatively. PROMs will be completed by the patients before and after surgery to assess their ability to detect the same changes in performance-based knee function measured by the sensors. Additionally, the study will investigate the correlation between the degree of knee alignment correction and postoperative performance-based knee function in participants after TKA.